2022
DOI: 10.1108/k-09-2021-0853
|View full text |Cite
|
Sign up to set email alerts
|

Acquiring supply chain agility through information technology capability: the role of demand forecasting in retail industry

Abstract: PurposeDespite the importance of demand forecasting in retail industry, its influence on supply chain agility has not been sufficiently examined. From a total information technology (IT) capability perspective, the purpose of this paper is to examine the antecedent of supply chain agility through retail demand forecasting.Design/methodology/approachCombining the literature reviews, the quantitative method of algorithm analysis was targeted at, and the firm data were processed on MATLAB.FindingsThis paper summa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 103 publications
0
3
0
1
Order By: Relevance
“…FMCG companies often operate in a complex environment characterized by high demand volatility, short product lifecycles, numerous SKUs (stock-keeping units) and intricate distribution networks [110]. These complexities are amplified by factors such as changing consumer preferences, globalization, regulatory requirements and the need to maintain a balance between supply and demand [111]. Managing this complexity is crucial for FMCG companies to ensure efficiency in the supply chain, minimize costs, optimize inventory and meet customer demands promptly.…”
Section: Managerial and Policy Implicationsmentioning
confidence: 99%
“…FMCG companies often operate in a complex environment characterized by high demand volatility, short product lifecycles, numerous SKUs (stock-keeping units) and intricate distribution networks [110]. These complexities are amplified by factors such as changing consumer preferences, globalization, regulatory requirements and the need to maintain a balance between supply and demand [111]. Managing this complexity is crucial for FMCG companies to ensure efficiency in the supply chain, minimize costs, optimize inventory and meet customer demands promptly.…”
Section: Managerial and Policy Implicationsmentioning
confidence: 99%
“…Models which do not use ML algorithms cannot get to know their customers more sincerely. Generally, these types of models cannot gain a deeper understanding of the system which is under consideration (Bai, 2022). While ML algorithms can learn the connections and then set product development and marketing initiatives related to customer behavior by collecting customer data, identifying behaviors and relating them to each other over time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this context, analyzing market demand history becomes crucial in understanding and explaining these dynamics (Robinson and Hsieh, 2016). Moreover, demand forecasting accuracy has been identified as a crucial factor in improving SC responsiveness and reducing costs, leading to an increasing number of studies emphasizing its importance (Friscia et al , 2004; Bai, 2022). The research conducted by Friscia et al (2004) demonstrated that the top-performing demand forecasters experienced significant advantages compared to their counterparts.…”
Section: Literature Reviewmentioning
confidence: 99%